Non-parabolic intergranular barriers in tin oxide and gas sensing - Aldao, Celso Manuel (2012)
Chemoresistive properties of crystalline solids strongly depend on the concentration of stoichiometric defects. In the case of tin oxide, oxygen vacancies are a case in point of such kind of defects. We address the problem of band bending and Schottky barrier formation in tin oxide. We approached the problem of charged native defects, oxygen vacancies, in a metal oxide in equilibrium with an oxygen containing ambient under three equivalent points of view. We focused on the non-parabolic barriers character that form at intergrains. Implications in gas sensing are discussed.